ALG13 Deficiency Associated with Increased Seizure Susceptibility and Severity. (15th June 2019) - Gao, Peng; Wang, Feng; Huo, Junming; Wan, Ding; Zhang, Jing; Niu, Jianguo; Wu, Ji; Yu, Baoli; Sun, Tao
Abstract: ALG13 (asparagine-linked glycosylation 13 homolog) encodes a crucial protein involved in the process of N-linked glycosylation, and abnormal N-linked glycosylation is considered an important risk factor that leads to neurological deficits and disorders. However, the causal relationship between ALG13 and epilepsy remains unknown. This study applied a kainic acid (KA)-induced epileptic mouse model to determine whether ALG13 deficiency resulted in increased susceptibility to and severity of epileptic seizures. This report found that the expression of ALG13 in the central nervous system (CNS) had histologically and cellular specificity, mainly in the neurons in the cortex and hippocampus, epilepsy commonly occurs. In addition, KA-induced seizures significantly affected the expression levels of ALG13 mRNA and protein in the forebrain of wild-type (WT) mice. KA-induced epileptic progressions were dramatically increased in Alg13 knockout (KO) mice, including prolonged electrographic seizures, strikingly increased mortality rates, and the severity of responses to epileptic seizures. Furthermore, KA-induced epilepsy-related pathological changes of the brain were predominantly exacerbated in Alg13 KO mice. This study also preliminarily explored the possible mechanisms of ALG13-involved epilepsy by showing hyperactive mTOR signaling pathways in the cortex and hippocampus of Alg13 KO mice. To the best of our knowledge, this report is the first evidence of the association between ALG13 and epilepsy in experimental animals. Highlights: KA-induced seizures significantly affect the expression of ALG13. ALG13 is co-expressed with neurons in hippocampus and cortex. ALG13 deficiency increases the epileptic susceptibility in drug-induced epileptic animal models. ALG13 deficiency dramatically exacerbated epilepsy related pathological changes of epileptic mice brain. The underlying mechanism ALG13 related epileptic activity is associated with hyperactivation of mTOR signaling pathways.